Effect of Entrepreneurship Training and Entrepreneurship Orientation on Business Performance of Asnafpreneur - Abdul Rani, Lebai Jaafar (2023)
The business landscape has always been dynamic, challenging entrepreneurs to adapt and innovate in order to sustain and enhance performance. Despite the growing body of literature on entrepreneurship training and orientation, empirical evidence on their combined influence on business performance, particularly among 'asnafpreneurs,' is scant. This study aims to bridge this gap by investigating the impact of entrepreneurship training and entrepreneurship orientation on the business performance of selected asnafpreneurs. Utilizing a quantitative research approach, data were collected from 100 'asnafpreneurs' through structured questionnaires. Multiple regression analysis was employed to analyze the relationships among the variables. The study's independent variables were entrepreneurship training and entrepreneurship orientation, while the dependent variable was business performance. The results indicate a significant positive relationship between entrepreneurship training and business performance. Additionally, entrepreneurship orientation was also found to contribute positively to business performance. These findings suggest that both training and orientation are critical factors that can significantly improve the performance metrics of businesses led by asnafpreneurs. This research provides valuable insights for policymakers, academicians, and practitioners interested in enhancing entrepreneurial success rates, particularly in the asnafpreneur sector. Future research could explore these relationships across different contexts and business types to offer a more comprehensive understanding of these dynamics.